Developing Musical Skills In Students Of Children's Music And Art Schools - Okhunjon Ilkhomjonugli Kimsanov (Euro Asian Journal Publishing, 2024)
The works of music created by our great ancestors have given spiritual strength to our people and children since time immemorial, calling them to friendship, honesty, purity, moral beauty, and joy of life. Therefore, the law was established by our state for our youth to have an impeccable status, especially in music and art schools, and wide opportunities were opened for them. The famous book "Avesta" and other written monuments, the traditions of the peoples of Central Asia, the archeological elements of weddings give a clear idea that the art of music was initially syncretic. Dervishes have long been part of the Zoroastrian prayer choir sung in temples
Keywords: education; syncretic; technology; innovation